Writing and print: two philosophical concepts to think about the creative process - Cares Villegas, Felicia (Arteterapia. Papeles de arteterapia y educación artística para la inclusión social, 2023)
On the essay A note on the magic board, Freud tried to make a comparison between a childish toy and the functioning of the psychic apparatus. However, it was not only a metaphor for a clinic concept. What we can see in that image is a subversive kind of thinking to create new knowledge. Through the concepts of the philosopher Jacques Derrida: ‘print’ (as a movement that keep, hold and is modified at the same time) and ‘writing’ (as inscription, a mark to sign the appearance of a human gesture that is signified in that very moment when it is produced), I try to show how the father of the psychoanalysis left a revolutionary way to think something we consider established and how it could be changed into something new. In the end of this text, I introduce a therapeutic perspective of the artistic language as a device. The thoughts of Derrida and Freud, let us observe the creative process as a force that bounce an established world
Keywords: writing-diferance-artistic creation-print.